Effective stakeholder management and project delivery: A case study on mondelez cocoa life project in Antwima Mponua District - Arhin, Jemima (2021)
A thesis submitted to the Department of Building Technology, College of Art and Built Environment, in partial fulfillment of the requirement for Degree of Master of Science.